Inventarisasi Makanan Jajanan di Sekolah Dasar Kecamatan Nanggalo Padang - Antoni, Pramita; Fridayati2, Lucy; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research early from perception of researcher about habit of elementary school student eat something of the home which fond of to consume food of jajanan in school. Habit of this eat something of the home often exploited by seller to draw attention children by selling is assorted food of jajanan nd also immeasurable processing technique. This research purpose is inventaritation food of jajanan pursuant to technique processing of food. 1) Moist Heat Cooking Technique 2) Dry Heat Cooking Techique.This research type is qualitative research, research location at elementary school exist in district of Nanggalo Padang. Data the use is obtained data direct the than the source of perceived. Object of this research that is foof of jajanan found on 25 elementary school in district of Nanggalo Padang. Result of research of seen that highest indicator is most food of jajanan use dry heat cooking technique, while indicator with low indicator is food of jajanan use moist heat cooking technique.Keywords : Inventoy, Food of Jajanan, Technique processing of food